2013
DOI: 10.5812/nephropathol.10656
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of selenium on cisplatin induced nephrotoxicity: A double-blind controlled randomized clinical trial

Abstract: Background: Renal injury is common following cisplatin infusion. Some agents have been used to attenuate cisplatin nephrotoxicity. However, except hydration, none of them has been proved to be effective. Objective: In this study selenium as an antioxidant supplement was tested on cisplatin induced renal injury. Patients and Methods: 122 cancerous patients (85 male and 37 female; age range of 14 to 82 years old) were enrolled to receive chemotherapy regimens consisting cisplatin. They were allocated into two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 18 publications
2
21
0
2
Order By: Relevance
“…4 We concluded that gender difference of cisplatin renal toxicity was related to the reninangiotensin system receptors in the kidneys. [4][5][6][7][8][9] Moreover, we recently found that vitamin C, vitamin E, or losartan have no ameliorative effects against cisplatin-kidney toxicity in presence of estrogen in ovariectomized rat model of cisplatin toxicity, 10 which is in agreement with our previous findings too. Hence, it is well established that there is a gender difference in the cisplatin renal toxicity in rat model.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…4 We concluded that gender difference of cisplatin renal toxicity was related to the reninangiotensin system receptors in the kidneys. [4][5][6][7][8][9] Moreover, we recently found that vitamin C, vitamin E, or losartan have no ameliorative effects against cisplatin-kidney toxicity in presence of estrogen in ovariectomized rat model of cisplatin toxicity, 10 which is in agreement with our previous findings too. Hence, it is well established that there is a gender difference in the cisplatin renal toxicity in rat model.…”
supporting
confidence: 82%
“…Hence, it is well established that there is a gender difference in the cisplatin renal toxicity in rat model. Indeed, it is well recognized that some conditions that lead to chronic kidney diseases are sex related too; [5][6][7][8][9][11][12][13] however, few studies published regarding gender difference in cisplatin renal toxicity . However, there still needs to be more investigations, mechanisms take part in cisplatin renal toxicity especially on gender difference.…”
mentioning
confidence: 99%
“…Johns et al (2012) concluded that cisplatin therapy had been shown to induce high levels of lipid peroxidation in lung cancer patients and could be assessed from the 8-isoprostane marker in overnight urine, with or without volume correction (Johns et al, 2012). Thus, the administration of antioxidants such as vitamin C, vitamin E, Silymarin, selenium, and so on before the administration of CDDP has been used to protect against kidney and liver toxicities (Ajith et al, 2009;Abdelmeguid et al, 2010;Ghorbani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They found that acute kidney failure occurred in 11.5% of patients treated with cisplatin, whereas in those pretreated with a single selenium tablet (400 mcg), no such cases were observed. 57 Similarly, Mix et al observed some protective influence of selenium treatment (selenomethionine, 1 week before as well as during therapy) in patients with inoperable, stage III non-small cell lung cancer undergoing concurrent chemoradiation (radiation, paclitaxel and cisplatin). 23 …”
mentioning
confidence: 99%